Systematic review of raloxifene in postmenopausal Japanese women with osteoporosis or low bone mass (osteopenia) - Fujiwara S (Dove Medical Press, 2014)
Saeko Fujiwara,1 Etsuro Hamaya,2 Masayo Sato,2 Peita Graham-Clarke,3 Jennifer A Flynn,2 Russel Burge41Hiroshima Atomic Bomb Casualty Council, Hiroshima, Japan; 2Lilly Research Laboratories Japan, Eli Lilly Japan K.K., Kobe, Japan; 3Global Health Outcomes, Eli Lilly Australia, Sydney, NSW, Australia; 4Global Health Outcomes, Eli Lilly and Company, Indianapolis, IN, USAPurpose: To systematically review the literature describing the efficacy, effectiveness, and safety of raloxifene for postmenopausal Japanese women with osteoporosis or low bone mass (osteopenia).Materials and methods: Medline via PubMed and Embase was systematically searched using prespecified terms. Retrieved publications were screened and included if they described randomized controlled trials or observational studies of postmenopausal Japanese women with osteoporosis or osteopenia treated with raloxifene and reported one or more outcome measures (change in bone mineral density [BMD]; fracture incidence; change in bone-turnover markers, hip structural geometry, or blood–lipid profile; occurrence of adverse events; and change in quality of life or pain). Excluded publications were case studies, editorials, letters to the editor, narrative reviews, or publications from non-peer-reviewed journals; multidrug, multicountry, or multidisease studies with no drug-, country-, or disease-level analysis; or studies of participants on dialysis.Results: Of the 292 publications retrieved, 15 publications (seven randomized controlled trials, eight observational studies) were included for review. Overall findings were statistically significant increases in BMD of the lumbar spine (nine publications), but not the hip region (eight publications), a low incidence of vertebral fracture (three publications), decreases in markers of bone turnover (eleven publications), improved hip structural geometry (two publications), improved blood–lipid profiles (five publications), a low incidence of hot flushes, leg cramps, venous thromboembolism, and stroke (12 publications), and improved quality of life and pain relief (one publication).Conclusion: Findings support raloxifene for reducing vertebral fracture risk by improving BMD and reducing bone turnover in postmenopausal Japanese women with osteoporosis or osteopenia. Careful consideration of fracture risk and the risk–benefit profile of antiosteoporosis medications is required when managing patients with osteoporosis.Keywords: bone density, fractures, osteoporotic, Japan, osteoporosis, raloxifene